Delivery of Open, Distance, and E-Learning in Kenya - Nyerere, Jackline K. A.; Gravenir, Frederick Q.; Mse, Godfrey S. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
The increased demand and need for continuous learning have led to the introduction of open, distance, and e-learning (ODeL) in Kenya. Provision of this mode of education has, however, been faced with various challenges, among them infrastructural ones. This study was a survey conducted in two public universities offering major components of ODeL, the University of Nairobi and Kenyatta University. These universities were purposely selected for the study, whose respondents included the students registered in ODeL and the lecturers and senior administrators involved. Analysis of the relevant documents was also undertaken, while library literature was reviewed on the integration of ODeL into the provision of education in Kenya. The study established that efficient and optimal delivery of ODeL in Kenya faces both economic and infrastructural challenges. However, strengthening the existing relevant structures would address some of the challenges.